النقد النحوي للرواية عند ابن فُورَّجة في شعر المتنبي - بابو, غياث (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
يُعدُّ ابن فورَّجة واحداً من كبار النقّاد النحويين الذين نقدوا شعر المتنبي، إذ حوى نقده أفكاراً ، وآراء نحوية تستحقّ الدراسة ، والاهتمام، وشكّل شعر المتنبي ميداناً خصباً للنقد النحوي من خلال المعركة النقدية التي قامت على شعره ، فحاول ابن فورَّجة من خلال حكمه النحوي تدعيم مذهبه ، أو دفع رأي، أو توضيح ما خالف قاعدة موضوعة ، أو الكشف عن مشكل في موضع ما في شعر المتنبي ، خاصّة عند تباين آراء الشرّاح ، واختلاف مذاهبهم وأقوالهم . ولاسيّما عند ابن جنّي . فالشعر كان ، ومايزال ، مصدراً مهماً في بناء القاعدة النحوية ، وإن امتزج في بعض الأحيان بمشكلات الرواة وعدم الدقة في النقل . ومن هنا تعددت الرّوايات والرّواة للشّعر، فشكّلت ظاهرة بارزة تحتاج إلى دراسة ، ومعرفة التأثير الذي يمكن أن تتركه على القواعد النحوية . إذ يُعدُّ النحو عنصراً أساساً في ثقافة من اهتمَّ بالشروحات الأدبية ، فكانت هذه الدراسة التي ركزت على جانب مهمّ من جوانب النقد النّحوي الذي طُبِّق على شعر المتنبي . Al-Wahidi is one of the greatest syntactic critics who have explained al-Mutanabbi's Anthology. His explanation contains concepts, and syntactic and critical opinions that deserve study and scrutiny. Al-Mutanabbi's poetry stands as a fertile domain for syntractic criticism as is apparent in the critical arena over his poetry. Through his syntactic judgement, al-Wahidi attempts to support a doctrine, oppose some point of view, elaborate on what violates a proposed principle, or uncover a certain problematic issue somewhere in al-Mutanabbi's poetry; specially when disagreement among critics' opinions appears, and dissimilarity among their doctrines and approaches materialises. Poetry was and is still one significant source to formulate the syntactic structure, even if it witnessed some unstability due to narrators' uncertainties, and imprecision of transference. So, narratives and narrators of poetry have varied, which has consequently created an obvious phenomenon that requires research, and study of the effect that may have on the syntactic rules. This is because syntax is one fundamental aspect of the culture of those interested in the literatry exegeses. This study comes to focus on one essential aspect of syntactic criticism that is already applied to al-Mutanabbi's poetry.